Comparative and competitive adsorption of heavy metals (Cd2+, Cu2+, Ni2+, Pb2+ and Zn2+) in aqueous medium onto chitosan-montmorillionite composite beads - Buscano, Sonia Ibarra (2009)
This study synthesized a novel adsorbent by blending chitosan with montmorillionite. The adsorption properties of heavy metals viz. Cd2+, Cu2+, Ni2+, Pb2+ and Zn2+ from single and multi-ion systems in synthetic aqueous medium was investigated in a batch manner at 25 ˚C, agitattion speed of 50 rpm, solution pH 4 and in dilute quantities (5-200 mg/1). Experiments conducted were based on the intial metal concentration, absorbent loading, and crosslinking with EGDE. Evaluation of isotherms using Langmuir and Freundlich yielded a good fit with both models (R2 >0.90) signifying that the adsorption sites are non-specific and non-uniform. Adsorption mechanism followed the pseudo-second kinetic model.
The multi-ion system appreciably enhanced uptake of all metal ions studied compared to the adsorption capacity of single ion system with respective increase of 16.04% for Pb2+; 223.37% for Cu2+; 192.90 % for Zn2+; 113.36% for Cd2+ and 241.99% for Ni2+. Data revealed a strong adsorbent selectivity towards Pb2+ against other divalent metal ions such as Cu2+, Cd2+, Ni2+ and Zn2+. Selectivity sequence was due to its different physico-chemical properties like ionic radius, ionic potential, hardness-softnessbehavior, coordination number, and atomic number/weight.
Thesis (M.S. Chemical Engineering)--University of the Philippines Diliman.
Keywords: Heavy metals -- Absorption and adsorption; Absorption and adsorption